Aerodynamic drafting in mass-start non-motorized sports: a systematic review - Beaumont, F.; Murer, S.; Bogard, F.; Polidori, G. (Journal of Biomechanics, 2025)
Drafting is a key strategy in sports, allowing athletes to reduce air or water resistance by positioning behind a competitor. This review examines drafting`s influence on sports performance, especially its aerodynamic and hydrodynamic effects. Studies confirm drafting is highly effective in cycling, running, and swimming, where drag and energy demands are significantly reduced. In cycling, for instance, drafting within a peloton can cut drag by up to 95%, enhancing speed and endurance. In swimming, trailing a competitor similarly lowers water resistance. Other sports, like kayaking and race walking, show promise, though research remains limited. Methods used to study drafting include wind tunnel tests, computational fluid dynamics (CFD), and field observations. Interest in drafting has surged, with 60% of studies published in the last decade, highlighting its growing impact on competitive sports. The review underscores drafting`s varied benefits within sports, calling for more standardized guidelines.